ملتقى المعماريين العرب - عيايدة, فداء (جامعة بوليتكنك فلسطين - معماري, 2021)
يعتبر التراث الثقافي والحضاري العربي من س ّجالً إلبداع األمة، ورمزاً من رموز عبقرتيها، وذاكرةً حافظةً مقّومات هُويتها الحضارية وخصوصيتها التي تتف ّرد بها بين الثقافات والحضارات. ويُعدّ الترا ُث المعمار ُّي عالمة مضيئة وثمرة مشعة لهذا اإلبداع الذي أسهمت به الحضارة اإلسالمية في إغناء الحضارات اإلنسانية وإثرائها، بما حملته من مظاهر جمالية وفنية، لت ّ َر العصور المختلفة، تمث واحتضنته من رموز ظلت به عنوانًا داالً على تطّور هذه الحضارة وتقدم بُناتها و ُصنَّاعها وعلمائها َع في ْب في ً المآثر التي ظلت شامخة مختلف بقاع العالم تشهد على نبوغ مهندسيها، وخلود فنها وعراقة رموزها. وتتجه العمارة على مستوى العالم في وقتنا الحالي نحو اتجاهات عديدة اذ تتأثر الحياة المعاصرة بمجموعة من المتغيرات والتوجهات الفكرية والثقافية، والنزعات التي يفرضها إيقاع العصر، بما يحمله من تسارع في األحداث، وتمازج باألفكار والحضارات والقيم الثقافية اإلنسانية، مما أنتج أفكار وتوجهات عديدة في اإلبداع المعماري، فكانت معظم تلك األفكار والتوجهات، كثيراُماال تنسجم مع قيم المجتمع العربي ذو التاريخ الحضاري العريق،بحيث أصبحت العمارة العربية غير ظاهرة على السطح وغير مهمة بالنسبة للمعمارين العرب فأصبحنا كمعماريين عرب بحاجة الى إعادة صياغة العمارة العربية واالهتمام بها والتركيز عليها في ظل ما تعانيه من الوهن وضياع مفرداتها. كانت هذه نقطة البداية النطالق فكرة مشروع ملتقى المعماريين العرب بحيث يشكل هذا المبنى المنبر إلعادة نشر العمارة العربية واحياء رموزها بلغة مواكبة للعصر. لذا ركز البحث على أهمية مفهوم العمارة المعاصرة، ذات الخصوصية المحلية العربية اإلسالمية، وأن تصبح األفكار المعمارية المعاصرة نابعة من فهم عميق وأصيل برؤية محلية، متوازنة مع إمكانات الحاضر وأصالة إلعادة إحياء العمارة العربيه انطالقا ، بحيث يكون هذا المبنى ً الماضي، ونظرة للمستقبل، ويسعى المشروع من المعماريين أنفسهم وجهه لكل المعماريين العرب، وبناء عليه تم اختيار مدينة القدس لتكون مركزا لهذا المبنى المتفرد بالعالم العربي، لموقعها المتوسط بالنسبة للعالم العربي واإلسالمي ولما لها من أهمية تاريخية ودينية أيضا العمارة العربية في القدس مميزة وقد مر عليها اغلب الحقب العربية واإلسالمية وتحتوي على ثروة معمارية غنية بالتفاصيل المعمارية العربية. The Arab cultural and civilizational heritage is considered a record of the nation's creativity, a symbol of its genius, a memory that preserves its values, and a component of its civilizational identity and its peculiarity that makes it unique among cultures and civilizations. The architectural heritage is a bright sign and of this creativity, through which the Islamic civilization contributed to enriching human civilizations, according to the aesthetic and artistic appearances it carried, it also embraced it as a symbol that has remained a title indicating the development of this civilization. Which made its scientists and makers at the forefront through different ages, which was exemplified by the exploits that remained lofty in various parts of the world, as a testament to the brilliance of their engineers. In addition to the eternity of its art and the legacy of its symbols. Architecture is moving in the world at the present time towards many directions, as contemporary life is affected by a set of intellectual and cultural variables and trends imposed by the rhythm of the age through the acceleration of events that it carries, in addition to the blending of ideas, civilizations, and cultural and human values, which produced many ideas and trends in architectural creativity Most of these ideas and trends were not in harmony with the values of the Arab society who have a long history of civilization, so that Arab architecture became invisible on the surface and unimportant for Arab architects, so we, as Arab architects, need to reformulate Arab architecture, pay great attention and focus on it in light of the weakness and loss of vocabulary. This was the starting point for launching the idea of the Arab Architects Forum, so that this building represents the platform for re-spreading Arab architecture and reviving its symbols in a language that keeps pace with the times. Therefore, this research focused on the importance of the concept of contemporary architecture, with local Arab-Islamic peculiarities, And to keep contemporary architectural ideas stemming from a genuine understanding with a local vision, balanced with the potential of the present and the originality of the past, and a view of the future, and the project seeks to revive Arab architecture based on the architects themselves, So that this building becomes a destination for all Arab architects, and accordingly, the city of Jerusalem was chosen to be the center of this unique building in the Arab world, for its central to the Arab and Islamic world and because of its historical and religious importance as well.in addition, Arab architecture in Jerusalem is distinctive, and most of the Arab and Islamic eras passed over Jerusalem, so it contains an architectural wealth rich with Arab architectural details
CD , no of pages 50 , معماري 3/2021
Keywords: المعماريين العرب - ملتقيات